Bibliometrics of electronic journals in information science - Donald T. Hawkins (Information Research: An International Electronic Journal)
The bibliometric characteristics of electronic journals (e-journals) covering the field of information science have been studied. Twenty-eight e-journals were identified and ranked by number of articles on the subject they published. A Bradford plot revealed that the core is not well developed yet, but it will likely contain six journals. The publication of information science articles in e-journals began modestly in 1995 with 26 articles, but it has risen to approximately 250 articles per year. The most prolific authors are identified. The vast majority of them are located in the United States or United Kingdom. Only 26 articles have authors from more than one country, showing that electronic technology has not yet strongly influenced international collaboration. About 2/3 of the articles originate in academic institutions. Common topics of e-journal articles in information science include electronic information, electronic publishing, virtual (digital) libraries, information search and retrieval, and use of the Internet. Seven online databases cover these e-journals; Information Science Abstracts is the only one to cover all 28 journals, and it has the highest number of abstracts from them - over 1,100.